A potential role for zinc in restless legs syndrome. Issue 4 (11th November 2020) - Chen, Pan; Bornhorst, Julia; Patton, Stephanie; Bagai, Kanika; Nitin, Rachana; Miah, Mahfuzur; Hare, Dominic J; Kysenius, Kai; Crouch, Peter J; Xiong, Lan; Rouleau, Guy A; Schwerdtle, Tanja; et al.
Abstract: Study Objectives: Evaluate serum and brain noniron metals in the pathology and genetics of restless legs syndrome (RLS). Methods: In two independent studies (cohorts 1 and 2), in which subjects either remained on medications or tapered off medications, we analyzed serum levels of iron, calcium, magnesium, manganese, copper, and zinc both in RLS patients and controls, and assessed the prevalence of the MEIS1 and BTBD9 risk alleles previously established through genome-wide association studies. Human brain sections and a nematode genetic model were also quantified for metal levels using mass spectrometry. Results: We found a significant enrichment for the BTBD9 risk genotype in the RLS affected group compared to control ( p = 0.0252), consistent with previous literature. Serum ( p = 0.0458 and p = 0.0139 for study cohorts 1 and 2, respectively) and brain ( p = 0.0413) zinc levels were significantly elevated in the RLS patients versus control subjects. Conclusion: We show for the first time that serum and brain levels of zinc are elevated in RLS. Further, we confirm the BTBD9 genetic risk factor in a new population, although the zinc changes were not significantly associated with risk genotypes. Zinc and iron homeostasis are interrelated, and zinc biology impacts neurotransmitter systems previously linked to RLS. Given the modest albeit statistically significant increase in serum zinc of ~20%, and the lack of association with two known genetic risk factors, zinc may not represent a primary etiology for the syndrome. Further investigation into the pathogenetic role that zinc may play in restless legs syndrome is needed.